2009
DOI: 10.1101/gad.1737809
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Mph1 helicase dissociates Rad51-made D-loops: implications for crossover control in mitotic recombination

Abstract: Eukaryotes possess mechanisms to limit crossing over during mitotic homologous recombination, thus avoiding possible chromosomal rearrangements. We show here that budding yeast Mph1, an ortholog of human FancM helicase, utilizes its helicase activity to suppress spontaneous unequal sister chromatid exchanges and DNA double-strand break-induced chromosome crossovers. Since the efficiency and kinetics of break repair are unaffected, Mph1 appears to channel repair intermediates into a noncrossover pathway. Import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
342
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 232 publications
(367 citation statements)
references
References 88 publications
16
342
0
5
Order By: Relevance
“…Therefore, given the incomplete epistatic relationship between mph1 and rad54, it seems reasonable to place Mph1 at the Rad51-mediated strand invasion process, with a function distinct from that of Rad54. In addition, a recent study by Prakash et al (2009) has indicated that Mph1 is involved in dissolving D-loop structures, independently of Srs2 and Sgs1, in order to attenuate cross-over events. …”
Section: Mph1 Probably Acts At a Stage After Initiation Of Recombinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, given the incomplete epistatic relationship between mph1 and rad54, it seems reasonable to place Mph1 at the Rad51-mediated strand invasion process, with a function distinct from that of Rad54. In addition, a recent study by Prakash et al (2009) has indicated that Mph1 is involved in dissolving D-loop structures, independently of Srs2 and Sgs1, in order to attenuate cross-over events. …”
Section: Mph1 Probably Acts At a Stage After Initiation Of Recombinationmentioning
confidence: 99%
“…A wide genetic analysis placed MPH1 in a pathway dedicated to the error-free bypass of DNA lesions via HR (Schürer et al, 2004). A recent work by Prakash et al (2009) described the ability of purified Mph1 to bind D-loop structures and to unwind these DNA structures, although it is probably not its only function since it would not explain the mph1 mutator phenotype (Scheller et al, 2000). S. cerevisiae Mph1 shows sequence similarity to human FANCM and the archaeabacterial Hef (Komori et al, 2002;Meetei et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…FANCM protein in plants and its homologs in fission (Fml1) and budding yeast (Mph1) have been implicated in anticrossover control during meiotic HR and in vegetative cells, respectively (Prakash et al 2009;Crismani et al 2012;Lorenz et al 2012). Budding yeast Mph1 has been shown to dissociate nascent D-loops in reconstituted reactions with Rad51 and Rad54 as well as protein-free D-loops in a helicase-dependent manner (Prakash et al 2009).…”
Section: Reversibility Of Extended D-loops: a Step In Sdsa And A Mechmentioning
confidence: 99%
“…Budding yeast Mph1 has been shown to dissociate nascent D-loops in reconstituted reactions with Rad51 and Rad54 as well as protein-free D-loops in a helicase-dependent manner (Prakash et al 2009). Further analysis will be required to determine the exact mechanism used by these enzymes to avoid crossovers.…”
Section: Reversibility Of Extended D-loops: a Step In Sdsa And A Mechmentioning
confidence: 99%
“…An activity shared by Mph1 and its orthologs is the dissociation of DNA D-loop structures, a function important in limiting crossovers during mitotic recombination (21)(22)(23). In addition, Fml1, FANCM, and Hef can catalyze the regression or unwinding of replication forks, which can potentially lead to recombination (22)(23)(24).…”
mentioning
confidence: 99%